Study of network topology poisoning attacks in Software-Defined Networks - Yong, Shiuanlit (2017)
In this day and age, network has been playing a crucial role in everyone’s daily life. Cloud computing, network communication (intranet and extranet), information management and technologies have been evolving daily business operations and Information Technology industry as well. With the innovation and emergence of the network computing, there have been an increasing trend for network research and development, in order to explore new opportunities with effective network operations and management, meeting the different needs on various users within multiple industries. SDN – Software Defined Networking, has been introduced and researched, in effort of achieving the customized network for different type of users, while simplifying the whole network control and architecture, for the ease of network management. With the highlighted demands of the SDN, many researchers and developers are targeting to continue with the possible enhancement in this area; yet, often missed out in evaluating the risks and vulnerability involved with the SDN network security, particularly the SDN poisoning. Thus, in this report, we would be exploring and focusing on reviewing SDN, and discuss on the strength of SDN, followed by its vulnerability towards poisoning attacks.